A Comprehensive History of India : Prehistory of India (Vol. I, Part 1) - Dhavalikar, M.K., (Brill | Manohar Publishers & Distributors, 2023)
The prehistoric phase forms the longest period in human history covering a few millennia whereas the knowledge of writing which could be used for the reconstruction of history, was acquired by man only five thousand years ago. The development of human culture can be properly understood only by studying the prehistoric past. The antiquity of man now goes back to 3.6 million years, and since then man has been progressing in the face of all odds. Man the hunted became man the hunter, later acquired the technique of food production which further led to sedentary existence, fashioned artefacts to cope with environment, learnt the use of metals and established trading contacts, finally leading to urbanization. In India the first Stone Age tools were discovered in Tamil Nadu which have recently been dated to 1.5 million years (but could not be included in the present volume as it was too late). The proper study of prehistory received a boost in the post-Independence period. Hundreds of prehistoric sites have since been discovered almost all over the country, even in the north-east which was archaeologically a terra incognita till now. Systematic excavations have been carried out and the data scientifically analysed, stages of evolution of culture from food gathering to food producing have been traced and the further development into the glorious Indus - Harappan - civilization has also been critically reviewed. The volume includes contributions from acknowledged experts in the field. Greater emphasis has been laid on scientific evidence which brings out the role of environment in the evolution of cultures. The study ends with the advent of Aryans which is one of the knottiest of issues in human history.